Teaching about ozone layer depletion in Turkey: pedagogical content knowledge of science teachers - Bozkurt, Orcun; Kaya, Osman Nafiz (Sage Publications Ltd, 2008)
The purpose of this study was to investigate the pedagogical content knowledge of Prospective Science Teachers (PSTs) on the topic of ozone layer depletion. In order to explore PSTs' subject matter knowledge on ozone layer depletion, they were given a form of multiple-choice test where they needed to write the reasons behind their answers. This test was completed by 140 PSTs in their final year at the College of Education. Individual interviews were carried out with 42 randomly selected PSTs to determine their pedagogical knowledge about ozone layer depletion. Data were obtained from the study which indicate that the PSTs did not have adequate subject matter and pedagogical knowledge to teach the topic of ozone layer depletion to middle school students. It was also evident that the PSTs held various misconceptions related to ozone layer depletion. PSTs' inadequate pedagogical knowledge was found in the areas of the curriculum, learning difficulties of students, and instructional strategies and activities. This study provides some pedagogical implications for the training of science teachers.
Keywords: Conceptions; Matter